2009
DOI: 10.1021/jm9009229
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Modes of Enzyme Inhibition in a Homologous Structure−Activity Series

Abstract: A docking screen identified reversible, non-covalent inhibitors (e.g. 1) of the parasite cysteine protease cruzain. Chemical optimization of 1 led to a series of oxadiazoles possessing interpretable SAR and potencies as much as 500-fold greater than 1. Detailed investigation of the SAR series subsequently revealed that many members of the oxadiazole class (and surprisingly also 1) act via divergent modes of inhibition – competitive or via colloidal aggregation – depending on the assay conditions employed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
73
0
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 24 publications
0
73
0
1
Order By: Relevance
“…The inhibition of cruzain enzymatic activity by all compounds was measured using a competition based assay with the substrate Z-PheArg-aminomethylcoumarin (Z-FR-AMC) [41]. All compounds were screened at 50 µM, and only compounds having an inhibition value of >70% were chosen to determine IC 50 values.…”
Section: Cruzain Inhibition Activitymentioning
confidence: 99%
“…The inhibition of cruzain enzymatic activity by all compounds was measured using a competition based assay with the substrate Z-PheArg-aminomethylcoumarin (Z-FR-AMC) [41]. All compounds were screened at 50 µM, and only compounds having an inhibition value of >70% were chosen to determine IC 50 values.…”
Section: Cruzain Inhibition Activitymentioning
confidence: 99%
“…2,4 Although high hit rates may be useful for diagnosing NSI, our collective HTS data have shown that hit rates can differ substantially even within the same enzyme class, in a manner that is not due to NSI. The challenge to predict enzyme susceptibility to nonspecific inhibition is illustrated by the diverse inhibitory profiles among caspase family members (-1, -3, -6, -7, and -8) in our first case study.…”
Section: Nonspecific Inhibition Is Enzyme Isoform and Protein Construmentioning
confidence: 89%
“…2 Over the past decade, significant progress has been made, mostly by the academic research team of Shoichet, to clarify the mechanisms of nonspecific inhibition. Much of this work proved that promiscuous inhibitors physically interact with protein targets but do so by forming colloidal aggregates at micromolar compound concentration in an aqueous environment.…”
Section: Introductionmentioning
confidence: 99%
“…For cell-based assays, membrane permeability might also influence experimental data. Additional accounts of problems with experimental data have appeared in the recent literature [183,184].…”
Section: Biological Datamentioning
confidence: 99%